First record of the subgenus Megachelonus Baker, 1926 (Hymenoptera: Braconidae: Cheloninae, genus Chelonus Panzer, 1806) for the Afrotropical region (southwestern region of Saudi Arabia), with the description of a new species - Soliman, Jahmed M.; Dhafer, Hathal M. Al; Gadallah, Neveen S. (Zootaxa, 2025)
The subgenus Megachelonus Baker, 1926 of the cosmopolitan genus Chelonus Panzer, 1806 is recorded for the first time in the Afrotropical region, in a coffee orchard in Jazan (southwestern Saudi Arabia). A new species, Chelonus (Megachelonus) arabicus Soliman & Gadallah, is described and illustrated.